2010
DOI: 10.1103/physreve.81.036408
|View full text |Cite
|
Sign up to set email alerts
|

Collimation of dense plasma jets created by low-energy laser pulses and studied with soft x-ray laser interferometry

Abstract: The physical mechanisms driving the collimation of dense plasma jets created by low-energy ( approximately 0.6 J) laser pulse irradiation of triangular grooves were studied for different target materials using soft-x-ray interferometry and hydrodynamic code simulations. The degree of collimation of jets created by irradiating C, Al, Cu, and Mo targets at intensities of I=1x10(12) W cm(-2) with 120 ps laser pulses was observed to increase significantly with the atomic number. Radiation cooling is found to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A number of experiments have taken place in recent years to investigate jet propagation. These have demonstrated the propagation of a jet moving into an ambient medium, either stationary (Nicolaï et al 2008;Foster et al 2005;Ampleford et al 2005) or in the form of a plasma crosswind (Lebedev et al 2004), and an increase in jet collimation due to radiative cooling (Shigemori et al 2000;Lebedev et al 2002;Purvis et al 2010). The work presented here is aimed at studying the effects of radiative losses on the collimation of plasma jets.…”
Section: Introductionmentioning
confidence: 99%
“…A number of experiments have taken place in recent years to investigate jet propagation. These have demonstrated the propagation of a jet moving into an ambient medium, either stationary (Nicolaï et al 2008;Foster et al 2005;Ampleford et al 2005) or in the form of a plasma crosswind (Lebedev et al 2004), and an increase in jet collimation due to radiative cooling (Shigemori et al 2000;Lebedev et al 2002;Purvis et al 2010). The work presented here is aimed at studying the effects of radiative losses on the collimation of plasma jets.…”
Section: Introductionmentioning
confidence: 99%
“…They were also motivated by the fact that similar, earlier NOVA experiments produced puzzling results, raising the question whether radiation-hydrodynamics codes might be inadequate to model the experiment and collisionless Particle-In-Cell (PIC) codes might be needed instead(WAN). GRAVA and later work by the same collaboration [31,32] showed that radiation-hydrodynamic codes are able to model this kind of experiment, and for a variety of different target elements.…”
Section: Comparison To Grava Et Al 2008mentioning
confidence: 97%
“…The HYDRA calculations were performed assuming Local Thermodynamic Equilibrium 5 and utilized the temporal measurements of the laser profile, the measured beam diameter, and the laser energy on the target to simulate the energy deposition into the target over time. HYDRA calculations were performed for two specific laser experiments corresponding to 10 14 and 10 16 Wcm -2 intensities.…”
Section: Simulationmentioning
confidence: 99%